THE RELATION OF 11-14 YEARS OLD STUDENTS MAP SKILLS AND THEIR ACHIEVEMENT LEVELS IN MATHEMATICS - Bülent AKSOY; Gökçe KILIÇOĞLU; Selman ABLAK (Zeitschrift für die Welt der Türken, 2015)
The purpose of this study is to elucidate the relation of 11-14 years old students mapping skills and their achievement levels in mathematics and investigate their mapping skills as regards to various variables. The study was carried out by the use of survey method. The data collection tool employed in the study was the achievement test developed by Sönmez (2010) upon 384 students studying in the central towns of Ankara province in 2012-2013 academic year. The sub problems of the study were solved by the use of t-test, One Way ANOVA and Pearson Correlation tests. The results of the study revealed that the scores of the students related to the all dimensions of the mapping skills of the students showed a positive in favor of the students studying in private schools .The mapping skills of the students did not show a significant difference in the dimensions of understanding the scale, location, and coordinate symbols. But there were significant differences in all other dimensions. Tukey Post Hoc test results showed that the differences were in favor of the 8th year students. Six mapping skills of the students at the secondary education level showed a medium level positive significant correlation with the mathematical achievement scores. In other words the increase in the mathematical achievement levels, increase their mapping skills in every dimensions.